2014
DOI: 10.5539/ass.v11n3p158
|View full text |Cite
|
Sign up to set email alerts
|

Features of Managers’ Personality Psychological Properties Relationship

Abstract: The aim of this article is researching psychological characteristics of Manager's personality. The leading approach of this research is to show close relationship of gender characteristics and significant features of Managers' personality. It has been shown that the most characteristic qualities of effective managers are communication skills, strong-willed qualities and also abilities to self-setting goals and organization of actions aimed at achieving them. Basic contributors indicating personality are: confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Similarly, Gabdreeva and Khalfieva (2016) conducted a study of all ranks of women managers (n = 152) and found that women adapt to different characteristics as they move up in management levels, whereas the low-level manager engages in activities and takes risks, the midlevel managers must resist negative social evaluation, reducing their willingness to take risks, and the top-level female managers have impressive communication skills, stress tolerance, and resiliency. Interestingly, the higher up a woman proceeds into the levels of management, the more androgynous they become.…”
Section: Perceptions Of Gender Characteristics In Leadersmentioning
confidence: 99%
“…Similarly, Gabdreeva and Khalfieva (2016) conducted a study of all ranks of women managers (n = 152) and found that women adapt to different characteristics as they move up in management levels, whereas the low-level manager engages in activities and takes risks, the midlevel managers must resist negative social evaluation, reducing their willingness to take risks, and the top-level female managers have impressive communication skills, stress tolerance, and resiliency. Interestingly, the higher up a woman proceeds into the levels of management, the more androgynous they become.…”
Section: Perceptions Of Gender Characteristics In Leadersmentioning
confidence: 99%